Conversion from twice daily tacrolimus capsules to once daily extended‐release tacrolimus (LCP‐Tacro): Phase 2 trial of stable liver transplant recipients. Issue 5 (26th March 2014) - Alloway, Rita R.; Eckhoff, Devin E.; Washburn, W. Kenneth; Teperman, Lewis W.
<x xml:space="preserve">Abstract</x> LCP‐Tacro is an extended‐release formulation of tacrolimus designed for once‐daily dosing. Studies in renal transplantation demonstrate greater bioavailability with similar safety and efficacy vs. twice‐daily tacrolimus capsules. In this phase 2 study, adult stable liver transplant patients on tacrolimus capsules (Prograf) twice‐daily were converted to tacrolimus tablets (LCP‐Tacro) once‐daily; patients continued on LCP‐Tacro once‐daily for days 8–21; target trough levels were 5–15 ng/mL; 24‐hour pharmacokinetic (PK) assessments were done on days 7 (baseline pre‐switch), 14, and 21. A 6 month extension study phase evaluated PK and safety following a total of 52 weeks of LCP‐Tacro. Fifty‐seven patients completed LCP‐Tacro dosing in the core study; 43 completed the extension phase. The mean conversion ratio was 0.71 (Prograf:LCP‐Tacro). PK data demonstrated consistent exposure (AUC) at the lower conversion dose. Cmax, Cmax/Cmin ratio, percent fluctuation and swing were significantly (P<0.001) lower and Tmax significantly (P<0.001) longer for LCP‐Tacro vs. Prograf. AUC24 and Cmin correlation coefficients after 7 and 14 days of therapy were ≥0.93. There were no significant differences in PK parameters at week 26 vs. 14. One patient experienced an unrelated serious adverse event (SAE) during the core study and discontinued. There were six unrelated SAEs in the extension and 1 possibly related (rejection) that resolved; there were 3 discontinuations due to AEs during the extension. In this study, patients were safely converted from Prograf twice‐daily to LCP‐Tacro. The greater bioavailability of LCP‐Tacro allowed for once‐daily dosing and similar (AUC) exposure at a dose approximately 30% less than the total daily dose of Prograf. LCP‐Tacro displayed significantly lower peak and peak‐trough fluctuations. LCP‐Tacro administered over one year was well tolerated with no new safety concerns. Liver Transpl 20:564–575, 2014. © 2014 AASLD.